2011
DOI: 10.3889/mjms.1857-5773.2011.0143
|View full text |Cite
|
Sign up to set email alerts
|

Adverse Effects of Organophosphorus Insecticides on Macrophage Activity in Persons at High Risk for Parasitic Infection

Abstract: Background: It has been suggested that acute exposure to pesticides altered the ability of macrophages to overcome the pathogen invasion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 23 publications
1
1
0
Order By: Relevance
“…and delayed the healing of cutaneous leishmaniasis lesions due to alterations in the immune response. This immunotoxicity could be associated with a significant increase in the level of the anti-inflammatory mediator arginase coupled with a significant decrease in the levels of the proinflammatory mediators NO and IFN-γ, as previously reported 18 .…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…and delayed the healing of cutaneous leishmaniasis lesions due to alterations in the immune response. This immunotoxicity could be associated with a significant increase in the level of the anti-inflammatory mediator arginase coupled with a significant decrease in the levels of the proinflammatory mediators NO and IFN-γ, as previously reported 18 .…”
Section: Discussionsupporting
confidence: 76%
“…Some epidemiological studies report that exposure to OP pesticides may increase the rate and risk of infections in rural populations 16 , exacerbating cutaneous leishmaniasis and inducing a low response to treatment in farmers exposed to chlorpyrifos, an OP pesticide that generates DETP and DEP 17 . In vivo studies showed that these effects on the immune response may be due to a decrease in the levels of plasma nitric oxide (NO) and interferon (IFN)-γ and to the increase in the activity of arginase, which explains the inability of macrophages (MΦ) to control the parasites or induce an adequate immune response against them 18 .…”
Section: Introductionmentioning
confidence: 99%